2021
DOI: 10.3390/biom11060830
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Production in Yeast Hosts: Current Status and Perspectives

Abstract: Resveratrol is a plant secondary metabolite known for its therapeutic applications as an antioxidant, anti-cancer, anti-inflammatory, anti-aging, cardio-protective, and neuroprotective agent. Topical formulas of resveratrol are also used for skin disease management and in cosmetic industries. Due to its importance, high resveratrol production is urgently required. Since the last decade, intensive efforts have been devoted to obtaining resveratrol from microorganisms by pathway and metabolic engineering. Yeasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…It is further identified as a phytoalexin (Zhou et al, 2021). The reaction between p-coumaroyl-coenzyme A and three malonyl-coenzyme A molecules is accomplished by RES synthase (modulated by defense system of the plant) in shikimic acid pathway to form RES (Ibrahim et al, 2021). Cis and trans structure of RES, free or attached to a glucose molecule, has been obtained.…”
Section: Chemistry Of Resmentioning
confidence: 99%
“…It is further identified as a phytoalexin (Zhou et al, 2021). The reaction between p-coumaroyl-coenzyme A and three malonyl-coenzyme A molecules is accomplished by RES synthase (modulated by defense system of the plant) in shikimic acid pathway to form RES (Ibrahim et al, 2021). Cis and trans structure of RES, free or attached to a glucose molecule, has been obtained.…”
Section: Chemistry Of Resmentioning
confidence: 99%
“…To synthesize resveratrol, one molecular p ‐coumaryl‐CoA and three molecular malonyl‐CoA are required. In addition to substrates, one step reaction based on stilbene synthase (Melkus et al, 2020) or multistep process (Ibrahim et al, 2021) based on chalcone synthase (CHS) and chalcone isomerase (CHI) could catalyze the up‐mentioned reaction. The implement of producing resveratrol can be achieved by engineering 4CL and STS.…”
Section: P‐coumaric Acid Derivativesmentioning
confidence: 99%
“…For instance, E. coli has been engineered to produce various phenolics, including resveratrol [ 116 ], a well-known antioxidant compound found in grapes and red wine. It was initially believed that resveratrol was only produced by plants, but later studies revealed that certain species of bacteria and fungi can also synthesize this compound (e.g., Saccharomyces cerevisiae ) [ 117 , 118 , 119 ]. By introducing specific genes encoding enzymes involved in phenolic biosynthesis, researchers have successfully developed bacterial strains capable of producing these compounds; Yeast production: certain strains of yeast, such as Saccharomyces cerevisiae , have been engineered to produce phenolic compounds [ 117 , 118 , 119 ].…”
Section: Microbial Natural Products Via Fermentation and Their Potent...mentioning
confidence: 99%
“…It was initially believed that resveratrol was only produced by plants, but later studies revealed that certain species of bacteria and fungi can also synthesize this compound (e.g., Saccharomyces cerevisiae ) [ 117 , 118 , 119 ]. By introducing specific genes encoding enzymes involved in phenolic biosynthesis, researchers have successfully developed bacterial strains capable of producing these compounds; Yeast production: certain strains of yeast, such as Saccharomyces cerevisiae , have been engineered to produce phenolic compounds [ 117 , 118 , 119 ]. Through genetic modifications, key enzymes involved in the phenolic biosynthetic pathway can be introduced into the yeast, enabling them to convert simple precursors into desired phenolic compounds.…”
Section: Microbial Natural Products Via Fermentation and Their Potent...mentioning
confidence: 99%